PENERAPAN MEDIA FLSH CARD DALAM PEMBELAJARAN BAHASA ARAB MATERI ASMAUL HAYAWANAT UNTUK MENINGKATKAN DAYA INGAT MUFRODAT DI KELAS III MI ROUDLOTUL JANNAH BORO JABUNG - Intan Pujiati; Muhammad Hanief; Lia Nur Atiqoh Bela Dina (JPMI: Jurnal Pendidikan Madrasah Ibtidaiyah, 2019)
Learning arabic in schools is often indicated by the problem of students’ low memory of mufrodat, this can be due to less interesting learning and less intersest in students. Therefore, the teacher’s role is very important in choosing and implementing appropriate learning media and also effective for students. This class of action research aims to describe and analyze the application of Flash Card media to improve mufrodat/ vocabulary memory in learning Arabic Asmaul Hayawanat material and the subject of this research are teachers and third grade students at MI Roudlotul Jannah Boro Jabung. Data taken is by observing the results of observations in each cycle, documentation, test to measure the increase in memory of other students then the data is processed quantitatively and described qualitatively. The result showed that the application of Flash Card media in learning Arabic Language material Asmaul Hayawanat was able to improve memory mufrodat.Keywords: Learning arabic, Flash Card media, memory of mufrodat,